Isolation and Identification of Candida Spp. from non-pregnant Infection woman's with Candidiasis - Dayea, Esraa Zeman (Medical Science Journal for Advance Research, 2023)
Due to their global dominance as the most common opportunistic mycoses, Candida species are important in medicine. the commonness of C. The incidence of Candida albicans and other species has significantly increased over the past few decades. These studies looked examined the ability of a vulvovaginal sample to isolate and identify Candida species as well as how different antifungal drugs, such as Amphotericin B, Nystatin, Itraconazole, Clotrimazole, and Ketoconazole, affected different Candida strains. Thirty out of fifty non-pregnant women who visited Al-Zahra Hospital and displayed symptoms and signs of candidial vulvovaginitis had their vaginal Candida spp. collected. They were between 20 and 35 years old. Direct microscopic examination, mycological analysis, and plating on sabrouaud dextrose agar (SDA) were were performed on all vaginal swabs. SDA was then incubated for 48 hours at 37°C. The Candida isolates were identified to the spp. level using the Vitek 2 Compact System, growth morphology, germ tube tests, and conventional staining techniques. The findings revealed the presence of C. albicans (66.6%), C. tropicalis (26.6%), and C. krusei (6.6%).